Child malnutrition as a poverty indicator: An evaluation in the context of different development interventions in Indonesia - Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2005)
There is no international consensus on what poverty is and how it should be measured. The most commonly used poverty indicator, income level, is limited as it ignores the multidimensional character of poverty. Because the choice of an indicator reflects societal values and developmental goals, and because what gets measured gets attention from policy makers and society, the choice of a poverty indicator is important. It sets priorities for policies and programs and determines outcomes of development. The paper reviews qualifications of a good indicator and proposes child malnutrition as an appropriate poverty indicator. It points out that implications of allowing poverty to affect children go beyond individual children to the health, well being and productivity of future generations and of society as a whole. It finds child nutrition to be a more comprehensive than income level as it is reflective of desirable outcomes of development i.e. improvement in gender equality, intra-household distribution, and health environment quality. Using Indonesia as a case study, the paper evaluates the practicality of adopting child malnutrition as a poverty indicator for ADB's rural development projects. Strengths and weaknesses of three child malnutrition indicators: stunting, wasting, and underweight are reviewed in the context of different development interventions. The paper concludes that child malnutrition is highly relevant conceptually but the practical use as a poverty indicator varies by country due to the limitation on data availability. The paper proposes that child malnutrition be included as one of the millennium development goal indicators.
Keywords: 330; Armut; Messung; Mangelernährung; Kinder; Indonesien